A few reflections on current tax law - Mária Bujňáková (Prawo Budżetowe Państwa i Samorządu)
The paper deals with the current state of Slovak tax legislation in terms of its qualitative attributes. It emphasizes some of the negative features, especially the high frequency of amendments to the law, lack of clarity of legislation, lack of effort on the appropriate application of the criteria of fairness and ability to pay taxes, as well as excessive political influence on the tax law-making process and its destabilizing effect.